Systematic review of the diagnostic role of neutrophil to lymphocyte ratio in sarcoidosis: NLR and sarcoidosis - Ghasempour Alamdari, Masoumeh; Kalami, Niusha; Shojaan, Horieh; Aminizadeh, Sarina; Ghaedi, Arshin; Bazrgar, Aida; Khanzadeh, Shokoufeh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: To outline the observations of studies evaluating the prominence of Neutrophil to Lymphocyte Ratio (NLR) in sarcoidosis. Methods: The search was performed on PubMed, Scopus, and web of science up until November 21, 2021. Eventually, a number of 17 papers were incorporated into this review. Results: The results of this analysis showed no significant difference of NLR values between sarcoidosis patients and tuberculosis patients (SMD=-0.36, 95% CI= -0.92-0.21). The results showed high heterogeneity (I2=90.83%, p